Professor Emeritus Dato’ Dr. ‘AbdulHamīd AbūSulaymān (1936 – 18 August 2021): a retrospection by a student of life - Hassan @ Mohamed, Nor Jana (OFIIR-CENTRIS, 2024)
Professor Emeritus Dato’ Dr. ‘AbdulHamīd AbūSulaymān (Allāh yarḥamuhu) was an internationally renowned action- oriented Islamic scholar, thinker, educationalist and author of many books and articles on Islam, Islamisation of human knowledge and Ummatic reformation. Many consider him the “Innovative Builder” , “Visionary” and “Transformational Leader” of the International Islamic University Malaysia, and rightfully so. He was the second Rector of the University, a pioneer in her historical, intellectual, and socio-cultural landscapes.